2014
DOI: 10.18632/oncotarget.2169
|View full text |Cite
|
Sign up to set email alerts
|

H-Prune through GSK-3β interaction sustains canonical WNT/β-catenin signaling enhancing cancer progression in NSCLC

Abstract: H-Prune hydrolyzes short-chain polyphosphates (PPase activity) together with an hitherto cAMP-phosphodiesterase (PDE), the latest influencing different human cancers by its overexpression. H-Prune promotes cell migration in cooperation with glycogen synthase kinase-3 (Gsk-3β). Gsk-3β is a negative regulator of canonical WNT/β-catenin signaling. Here, we investigate the role of Gsk-3β/h-Prune complex in the regulation of WNT/β-catenin signaling, demonstrating the h-Prune capability to activate WNT signaling als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 31 publications
1
48
0
Order By: Relevance
“…In NSCLC cells, PGE 2 has been shown to increase expression of the EMT regulator ZEB1 [4, 5]. In a recent study, inhibition of β-catenin-dependent transcription renders NSCLC cells unable to migrate [47]. Our observations confirm that expression of ZEB1 is increased by PGE 2 and coincides with nuclear translocation of β-catenin and activation of β-catenin-dependent transcription.…”
Section: Discussionsupporting
confidence: 82%
“…In NSCLC cells, PGE 2 has been shown to increase expression of the EMT regulator ZEB1 [4, 5]. In a recent study, inhibition of β-catenin-dependent transcription renders NSCLC cells unable to migrate [47]. Our observations confirm that expression of ZEB1 is increased by PGE 2 and coincides with nuclear translocation of β-catenin and activation of β-catenin-dependent transcription.…”
Section: Discussionsupporting
confidence: 82%
“…2A). In parallel with this we also assessed another known property of PRUNE in enhancing cell migration using HEK293 cells, which display negligible levels of endogenous PRUNE expression (Carotenuto et al , 2014), with expression levels assessed by western blotting (Supplementary Fig. 3E).…”
Section: Resultsmentioning
confidence: 99%
“…Data are presented as mean ± standard error of two replicate experiments. Absence of endogenous expression of PRUNE in HEK293 cells and reduction of levels of expression of PRUNE after adenovirus infection of SHSY5Y cells was confirmed by western blotting as described previously (Carotenuto et al , 2014). Immunoblotting for the immunoprepicipitation and co-sedimentation assays were performed using the following antibodies: anti-β-Tubulin (1 µg/ml; Abcam, ab15568), anti-alpha Tubulin (1 µg/ml; Abcam, ab15246), anti-Flag (1 µg/ml; Sigma, F3165), anti-Kinesin (1 µg/ml; Abcam, ab62105) and anti-GAPDH (1 µg/ml; Abcam, ab37168).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to phospho-diesterase activity, studies have identified that human PRUNE encodes a polyphosphatase activity (Tammenkoski et al 2008), whilst still more recent studies have also implicated PRUNE in WNT/β-catenin signalling via regulation of GSK-3β (Carotenuto et al 2014b). Whilst these are significant observations, it remains unclear what role the interaction with NME proteins may have on these processes, and clearly this requires further investigation.…”
Section: Prunementioning
confidence: 99%